Pengaruh Kepribadian, Locus Of Control Dan Kecerdasan Emosional Terhadap Kinerja Karyawan Di Pt. Pratama Agung Niaga Denpasar - Ni Komang Triayu Widiyastuti Widiyastuti; I Made Hedy Wartana; Ni Made Ernila Junipisa (Universitas Triatma Mulya, 2024)
To improve personality, locus of control and emotional intelligence on employee performance are things that companies must pay attention to. The present study endeavors to ascertain the following: 1) the effect of personality on employee performance at PT. Pratama Agung Niaga Denpasar, 2) the effect of locus of control on employee performance at PT. Pratama Agung Niaga Denpasar, 3) the effect of emotional intelligence on employee performance at PT. Pratama Agung Niaga Denpasar 4) find out the independent variables that have a dominant effect on employee performance at PT. Pratama Agung Niaga Denpasar. The method of research use is a quantitative method with a sample 90 employees. The sample sampling technique is saturated. The analysis techniques used are research instrument tests, classical assumptions, multiple linear analysis, t test, beta coefficient. The research results show the regression model Y = 3.894 + 1.273X1 + 0.061X2 + 0.223X3. From the results of this research it can be concluded that 1) job performance is direct and real impacted by personality; 2) job performance is direct and real impacted by locus of control; 3) job performance is direct and real impacted by emotional intelligence; 4) the personality variable has a significant impact on job performance. This is demonstrated by the standardized beta coefficient value of the personality variable, which is 0.758; locus of control is 0.089; and emotional intelligence is 0.235.